Analysis of the Rain Effects on Terrestrial Free Space Optics Based on Data Measured in Tropical Climate. - Ahmad Zabidi, Suriza; Islam, Md. Rafiqul; Wajdi, Al Khateeb; Ahmed Wathik, Naji (IIUM Press, 2011)
Free Space Optics (FSO) shows a great alternative as the solution for last mile problem where fiber optics is unavailable due to deployment time and cost constraint. However, the feasibility of using FSO system as communication link very much depends on local weather. Since tropical region experiences heavy rainfall, rain with high intensity is expected to affect the FSO link severely. Few prediction models have been proposed by ITU-R based on France and Japan’s measurement. This paper has compared rain attenuation predicted by models and data measured in Malaysia over Free Space Optical links for one year period. Prediction models are clearly unable to predict attenuation measured in tropical climate.